STUDENT-CENTERED APPROACHES TO TEACHING INJECTION SKILLS: INTEGRATING COMMUNICATION, VIDEO DEMONSTRATIONS AND MANNEQUIN PRACTICE - UMAMAHESWARI A; MANASHAA GP; SHANMUGA PRIYA S; BHUVANESWARI K (Asian Journal of Pharmaceutical and Clinical Research, 2025)
ABSTRACT Objectives: The objective of the study was to assess the effectiveness on video-based demonstration of injection procedural skills (Intramuscular [IM], Intravenous [IV], Intradermal [ID]) using mannequin and the performance of Phase II MBBS students. Methods: Phase II MBBS Students were taught about the steps in skill development of injection techniques (IM, IV, ID). Video demonstration of the injection procedure was done initially following which the facilitator demonstrated the same using the mannequins and students were allowed to practice individually under the guidance of facilitator. In internal assessment examination (IAE) 1 direct observation of procedural skills (DOPS), injection techniques (IM, IV, ID) were evaluated by the facilitator using data collection form and to analyze the effectiveness of the video-based demonstration feedbacks were also collected from the students. Remedial actions were taken based on the performance of students and feedback collected. Then, DOPS was evaluated again during IAE 2 and IAE 3 by the facilitator using a data collection form. Results: One-way analysis of variance analysis showed that there is a statistically significant improvement in the scores of the second and third practical internal assessment with the p<0.001. Conclusion: This study has shown that the video-based demonstration and recommendations implemented had helped the students in overcoming the mistakes and had shown improvement in their performance.